Analysis of Dumbo Catfish Culture (Clarias gariepinus) Using the Application of Biofloc System and Conventional System in Subdistrict Palas District Rumbai Pekanbaru City Riau Province - Syatari Retno Purwati; Zulkarnaini Zulkarnaini; Hendrik Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT              The research was conducted in 28 April – 18 May 2017 located in Subdistrict Palas, Rumbai District, Pekanbaru City, Riau Province. This study aims to determine the amount of investment capital, knowing the ratio of income and profits and analyze the feasibility of cultivation of catfish dumbo using the application of biofloc and conventional. The method used in this research is survey method with analysis of dumbo catfish culture business using the application of biofloc and conventional technology to Katon Jaya Group Cultivators. Business analysis in this research consists of total investment, production cost and business feasibility. Total investment spent on the breeding business of Catfish Dumbo biofloc IDR 42.820.000,-/harvest and conventional total investment of IDR 41.430.000,-/harvest. Production cost incurred in the business of enlargement of Catfish Dumbo biofloc IDR 28.070.000,-/harvest and cconventional of IDR 31.338.000,-/harvest. Cultivation of Dumbo catfish farming (Clarias gariepinus) in ponds in Palas village can be said to be feasible with the value of RCR > 1 that is biofloc 1.6 and conventional 1.3 with the value of FRR > 7% ie 38% biofloc and conventional 19.5% and the value of PPC for return of capital that is biofloc 2.6 period and conventional 5.1 period. Keywords: Business Analysiss, Clarias gariepinus, Feasibility Study, Palas Subdistrict.